Cognitive Restructuring Techniques to Improve Student Resilience - Ehdatul Puadi Siregar; Zadrian Ardi; Desi Sukenti (STAI Hubbulwathan Duri, 2025)
Resilience—the ability to adapt positively to adversity—has become a critical concern in educational psychology, particularly for high school students facing heightened academic and social stress. Cognitive restructuring (CR), a core component of cognitive-behavioral therapy, is known to enhance resilience by transforming maladaptive thoughts into constructive reasoning. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines to evaluate the effectiveness of CR techniques in improving student resilience. A total of 47 peer-reviewed articles published between 2015 and 2025 were analyzed. Studies were sourced from Scopus, ERIC, PsycINFO, and Web of Science, focusing on adolescents aged 15–18 in educational or counseling contexts. The synthesis revealed that CR interventions consistently enhanced emotional regulation, self-efficacy, and coping strategies, while also reducing cognitive distortions and academic stress. Techniques such as disputing irrational beliefs and reframing negative thoughts were effective in improving students’ problem-solving and perseverance. Group-based and digital CR implementations yielded particularly strong outcomes in resilience development. Findings support CR as a robust, evidence-based strategy for fostering resilience in adolescents. However, gaps remain regarding long-term effectiveness, cultural adaptation, and variability in intervention models. These limitations point to the need for longitudinal, cross-cultural, and experimental research to optimize implementation across diverse educational settings. Cognitive restructuring is a promising intervention to enhance psychological resilience among high school students, with significant implications for school-based counseling and mental health programs.